Stigma and the metaphorics of language : reading disease as dis-ease and reclaiming metaphor in selected contemporary South African literature - Schneider, Carron (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.